Economic Development of the Arab Countries : Selected Issues. (International Monetary Fund, 1993)
This volume, edited by Said El-Naggar, is the fifth in a series of seminars dealing with economic issues of particular importance to the Arab countries. Held in Manama, Bahrain, in February 1993, it covered topics pertaining to economic development of the Arab countries in the nineties. The seven papers that were presented comprised economic reform in the Arab countries, including particularly structural issues; investment policies and capital flows; inter-Arab labor movements; environment and development; development of human resources; and European economic integration. An overview of the topics is presented by the seminar moderator, Said El-Naggar.